RISK INDICATORS AMONG MEDICAL PERSONNEL WORKING IN MRI UNITS: HYGIENIC AND EPIDEMIOLOGICAL ASSESSMENT - Mirsagatova Movluda Riksillayevna (Web of Journals Publishing, 2025)
Medical personnel working with magnetic resonance imaging (MRI) are routinely exposed to complex occupational factors, including strong static magnetic fields (1.5–3 T), gradient fields, radiofrequency (RF) radiation, high-intensity acoustic noise (90–120 dB), and micro-leakage of cryogenic gases. Epidemiological studies conducted over the past two decades indicate an increase in risk indicators among MRI staff, such as headaches, disrupted sleep rhythms, reduced heart rate variability, visual–spatial discomfort, cognitive fatigue, altered stress hormones, and micro-damage to hearing. This analytical study evaluates major physiological, psychophysiological, and hygienic risk indicators identified among MRI personnel based on scientific evidence and proposes modern preventive strategies for this occupational group.
Keywords: Magnetic resonance imaging, electromagnetic field, medical personnel, occupational risk, cognitive fatigue, audiological impairment, hygienic assessment, physiological indicators.